Genotype and environment interactions of yield contributing characters of field mustard (Brassica rapa L.) (Bangladesh Journal of Botany, 2023)
Genotype-environment interaction is the norm of reciprocal action that determines the relationship between gene and environmental factors. Gene and environment interaction takes place when different environments affect the genotypes and vice versa. The investigation portrays the interaction between genes and environments of yield contributing characteristics of eleven genotypes of field mustard. Three  seeding-time environments, viz., early, late, and very late of eleven mustard genotypes were laid out with three replications in a randomized complete block design. Among the three environments, which one was favorable and which was not was determined by their significant differences through a combined analysis of variance. The IPCA 1 (first interaction principal component axis) score of genotypes in the AMMI (additive main effects and multiplicative interaction analysis) of G×E interactions was estimated as an indication of the ability to respond to the environments and the performance with changing environments of the genotypes. Considering all the scores, Sonali Sharisha (SS-75), and BINA Sharisha-10 were found to be highly stable genotypes, while among the three environments, the environment-1 (early sowing) was found the best sowing time for raising and harvesting a good mustard crop.Bangladesh J. Bot. 52(4): 1055-1065, 2023 (December)